Histopathological Investigation of Four Populations of Abalone (Haliotis iris) Exhibiting Divergent Growth Performance - Copedo, JS; Webb, SC; Ragg, NLC; Venter, L; Alfaro, AC (Elsevier BV, 2023)
The black-foot abalone (pāua), Haliotis iris, is a unique and valuable species to New Zealand with cultural importance for Māori. Abalone are marine gastropods that can display a high level of phenotypic variation, including slow-growing or ‘stunted’ variants. This investigation focused on identifying factors that are associated with growth performance, with particular interest in the slow-growing variants. Tissue alterations in H. iris were examined using histopathological techniques, in relation to growth performance, contrasting populations classified by commercial harvesters as ‘stunted’ (i.e., slow-growing) and ‘non-stunted’ (i.e., fast-growing) from four sites around the Chatham Islands (New Zealand). Ten adults and 10 sub-adults were collected from each of the four sites and prepared for histological assessment of condition, tissue alterations, presence of food and presence of parasites. The gut epithelium connective tissue, digestive gland, gill lamellae and right kidney tissues all displayed signs of structural differences between the slow-growing and fast-growing populations. Overall, several factors appear to be correlated to growth performance. The individuals from slow-growing populations were observed to have more degraded macroalgal fragments in the midgut, increased numbers of ceroid granules in multiple tissues, as well as increased prevalence of birefringent mineral crystals and haplosporidian-like parasites in the right kidney. The histopathological approaches presented here complement anecdotal field observations of reduced seaweed availability and increased sand incursion at slow-growing sites, while providing an insight into the health of individual abalone and sub-populations. The approaches described here will ultimately help elucidate the drivers behind variable growth performance which, in turn, supports fisheries management decisions and future surveillance programs.
Keywords: Abalone; Food limitation; Haliotis iris; Histopathology; Kidney crystals; Sand incursion; 3109 Zoology; 31 Biological Sciences; 0608 Zoology; Entomology; 3109 Zoology; Animals; Fisheries; Gastropoda; New Zealand; Animals; Fisheries; New Zealand; Gastropoda